2019
DOI: 10.4049/jimmunol.1801443
|View full text |Cite
|
Sign up to set email alerts
|

Murine T Cell Maturation Entails Protection from MBL2, but Complement Proteins Do Not Drive Clearance of Cells That Fail Maturation in the Absence of NKAP

Abstract: Recent thymic emigrants that fail postpositive selection maturation are targeted by complement proteins. T cells likely acquire complement resistance during maturation in the thymus, a complement-privileged organ. To test this, thymocytes and fresh serum were separately obtained and incubated together in vitro to assess complement deposition. Complement binding decreased with development and maturation. Complement binding decreased from the double-positive thymocyte to the single-positive stage, and within sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…They found that deletion of NKAP in Treg cells and hematopoietic stem cells leads to cell death [28][29][30]. An interesting aspect that attracted us most was that NKAP knockdown induced increased lipid peroxidation in naive T cells [31] and a higher death rate in colon cancer cells [26]; these findings were similar to some of our research results on glioblastoma. In 2019, we reported that NKAP alters tumor immune microenvironment and promotes glioma growth.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…They found that deletion of NKAP in Treg cells and hematopoietic stem cells leads to cell death [28][29][30]. An interesting aspect that attracted us most was that NKAP knockdown induced increased lipid peroxidation in naive T cells [31] and a higher death rate in colon cancer cells [26]; these findings were similar to some of our research results on glioblastoma. In 2019, we reported that NKAP alters tumor immune microenvironment and promotes glioma growth.…”
Section: Introductionsupporting
confidence: 80%
“…Given that there was a higher lipid peroxidation level in NKAPdeficient naive T cells [31], we hypothesized that NKAP knockdown induced cell death by ferroptosis. Oxidized C11-BODIPY was generally used as a ferroptosis marker.…”
Section: Nkap Knockdown Induced Cell Death By Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, stabilized glutathione levels in normal cells provide protection against oxidative stress and ferroptosis-driven cellular damage. Lipid peroxidation may increase as a consequence of either a reduced GPX4 expression or a reduction in the level of its cofactor glutathione [ 32 ]. At the onset of ferroptosis, increased iron-dependent lipid ROS production overwhelm GPX4's ability to control polyunsaturated fatty acid peroxidation, resulting in aberrant control of lipid peroxides and hence peroxidation, which are hallmarks of ferroptosis and lead to cell death [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ferroptosis also exerts a direct impact on T cells themselves. One study demonstrated that T-cell clearance was mediated by lipid peroxidation and ferroptosis and that ferroptosis was the vital backup scavenger system that maintained T-cell homeostasis ( 114 ). With regard to T-cell immunity, another study demonstrated that T cell-specific GPX4 deficient mice had defective CD8 + T cell homeostasis in the periphery and a compromised defense ability against viral and parasitic infection.…”
Section: Ferroptosis’ Role In Tumor Immune Microenvironmentmentioning
confidence: 99%